Guia del pueblo : Alcance al núm. 37 - Fisher, George, 1795-1873 (Imprenta del Estado de Tamaulipas, dirijida por Juan Antonio Aguirre, 1831)
Includes letter and note by Jorge Fisher as well as letter from Manuel de Mier y Teran exonerating the former in the case of the seizure of the schooner Cañon.